Graduation, first semester of 2024 (VITAL, 2025)
On July 26, the graduation ceremony of the School of Medicine was held, in which 83 students received their medical degrees, 39 of them with honors and one Magna Cum Laude.
Keywords: Graduation; Academic performance; Physicians